MAN AND THE CONFLICTS OF LIFE - Romanell, Patrick (Universidad Autónoma de Nuevo León, 2021)
El PasoTHE GENERAL theme of this paper is the complexity of human life as a moral phenomenon. As everybody recognizes to a greater or lesser extent, conflicts of all sorts arise in daily conduct, making for or adding to the complexity of individual and social life. It certainly is no news to hear that we live at a time when we are so concerned with the recurring problem of national and international tensions, especially, that it is natural for us to be anxious about finding ways and means of removing their causes or at least of mitigating their bad effects. (Actually, it would be news indeed to hear the opposite for a change.)